PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN MENGGUNAKAN JASA â€œRUMAH LAUNDRYâ€ DI KECAMATAN PALU SELATAN - NINGSIH, VERA (Fakultas Ekonomi Universitas Tadulako, 2015)
The purpose of this study is to determine the influence of quality of service that consists of physical evidence (X1), empathy (X2), reliability (X3), responsiveness (X4) and assurance (X5) on consumer satisfaction using services